Emotionally Focused Couples Therapy and Spirituality - Merve Nurlu (Spiritual Psychology and Counseling)
Emotionally focused therapy was created as a couples therapy approach and has become a frequently used therapeutic approach these days. This approach, theoretically based on the understanding that the attachment relationship observed between mother and child characterized by proximity seeking and separation anxiety resembles the relationship observed between couples, aims to turn unhealthy attachment relationships between couples into healthy ones. This process is realized by revealing the implicit and hidden emotions that cause problem situations to occur and gaining awareness about these emotions. Different studies have shown spirituality to be a major factor both in forming and solving problem situations in therapy for couples who care about spiritual values. In particular, the meanings couples who attach importance to religious values attribute to marriage and the quality of the relations developed within this meaning can be handled within the framework of emotionally focused couples therapy. The purpose of this article is to explain how the therapy process proceeds when emotionally focused couples therapy is combined with spiritual values and to show which methods and techniques are used in the light of sample cases. In addition, the article aims to raise awareness on how to use this therapy approach, as it can be combined with Islamic elements, and investigates how to set an example in this regard. This study, which briefly introduces emotionally focused couples therapy, provides short examples of how to perform interventions while working with couples who seek counseling using religious or spiritual matters.